Naata . The Bond - Monteiro, Anjali; Jayasankar, K. P. (TATA Institute of Social Sciences, 2003)
Verzio FF Start: 00:56:00, End: 01:41:00 Mumbai is the city of contrasts: extreme richness and extreme poverty. It is a city of film stars and large slums. Two friends - Hindu Bhau Korde and Muslim Waqar Khan - live and work in a multi-ethnic neighbourhood of Dharavi, the largest slum in Asia. The making of a poster and an amateur film, initiated by the two friends, becomes an important step to unify the community and bring about ethnic amity. Hindus, Muslims, Sikhs, and Christians are played by children, each of them representing 'the other' religion. This work is part of other grass-roots programs for inter-religious amity. Yet Waqar and Bhau's work raises several uncomfortable questions for the filmmakers, so-called modern, middle-class, secular, urban beings. The meta-story of the film reflects on their own position of (im)partial observers/outsiders. By using abstract and anonymous everyday objects, standing in for detachment and reflection, the process of filmmaking itself becomes a subject of analysis.